The relict landslide in bimsoils in downtown Genova, Italy: a new modeling approach. Issue 1 (1st January 2023) - Napoli, M L; Barbero, M; Minuto, D; Morandi, L; Ullah, H
Abstract: Stability problems occurring in geological units with a block-in-matrix fabric are often analyzed with deterministic approaches and/or assuming block-in-matrix rocks/soils (bimrocks or bimsoils) to be homogeneous equivalent geomaterials. However, recent studies have demonstrated that since these formations are characterized by a great (dimensional, spatial and lithological) variability, reliable results can only be obtained if a stochastic approach accounting for different block arrangements and dimensions is used. This paper extends and improves a previous study from Minuto and Morandi (2015) to evaluate the stability of a relict landslide in bimsoil located in downtown Genova (Italy), where a deterministic approach and the traditional limit equilibrium method were used. In this work, different slope models with elliptical blocks of variable eccentricity, size and positions are generated by means of a stochastic approach and are analyzed with the FEM code RS2. Moreover, since the slope can be considered to be a bimsoil, interfaces between the blocks and matrix are introduced in order to better simulate the lower strength at the block/matrix contacts. The numerical analyses of the slope reveal that shallow failure surfaces have a higher probability of occurrence as compared to the deep failure surfaces considered by Minuto and Morandi (2015). Furthermore, lower safety factors are obtained when a block-matrix interface strength smaller than that of the matrix (i.e., a bimsoil) is simulated.